Catalytic Gas‐Phase Production of Lactide from Renewable Alkyl Lactates. (15th February 2018) - De Clercq, Rik; Dusselier, Michiel; Makshina, Ekaterina; Sels, Bert F.
Abstract: A new route to lactide, which is a key building block of the bioplastic polylactic acid, is proposed involving a continuous catalytic gas‐phase transesterification of renewable alkyl lactates in a scalable fixed‐bed setup. Supported TiO2 /SiO2 catalysts are highly selective to lactide, with only minimal lactide racemization. The solvent‐free process allows for easy product separation and recycling of unconverted alkyl lactates and recyclable lactyl intermediates. The catalytic activity of TiO2 /SiO2 catalysts was strongly correlated to their optical properties by DR UV/Vis spectroscopy. Catalysts with high band‐gap energy of the supported TiO2 phase, indicative of a high surface spreading of isolated Ti centers, show the highest turnover frequency per Ti site.